Epidemiological characteristics of liver transplant patients in a state of Western Brazilian Amazon - Ferreira, Bruna Barbosa; Amaral, Thatiana Lameira Maciel; Genzini, Tércio; Prado, Patrícia Rezende do (Brazilian Journal of Transplantation, 2014)
Purpose: To describe the epidemiological profile of liver-transplanted patients followed in the state of Acre. Methods: Cross-sectional study performed from April 2003 to July 2014, for which we used medical records of patients from Acre Hospital, Brazil. Data were collected from electronic medical records in a semi-structured questionnaire. Absolute and relative frequencies of categorical variables were performed. The bank was analyzed with the SPSS 17.0 software. Results: Total of 70 liver transplants along the studied period. The most frequent cause that led to the transplant were the hepatitis B virus and cirrhosis (77.1%), 81.4% were male and 64.3% were above 45 years old, 34.4% of patients waited less than a year for the transplant, 87.1% used the medication Tacrolimus, 81.0% of patients were living in the city of Rio Branco, 42.9% were transplanted at Hospital Bandeirantes in São Paulo; the major complication was the post-transplant recurrence of the Hepatitis C Virus, and 14.3% patients died. As to the donor organ, 83.9% were cadaverous, 56.6% were male, and the leading cause for the death was hemorrhagic stroke. Conclusion: Characterization of liver-transplanted patients aims to contribute to improve services for such patient to be taken to the health care and intervention of such problem.